K.H. Miskotte, Bijbels ABC - Reeling Brouwer, Rinse (NTT, 2020)
In the perspective of the forthcoming English translation of K.H. Miskotte's Biblical ABC's and therewith its foreseeable renewed appropriation, some aspects of this classical document in the Dutch history of theology deserve reconsideration. These aspects are successively: 1. Its genesis in a course for leaders of biblical reading groups in neighbourhoods all over the city of Amsterdam (1941), of which Miskotte himself afterwards didn't have a correct recollection; 2. Its background both in the method of the discovery of the Leitwortstil (M. Buber) or the Formgeheimnis of Biblical narratives (F. Rosenzweig) and in the, at least in Miskotte's perception, ‘Israelitish' tendency of K. Barth's doctrine of the divine perfections (1940); 3. Its earliest reception, in which J. Koopmans remarkably noticed, that ‘now' (i.e. under the German occupation of the Netherlands) ‘we don't have a Church anymore, apart from the form, in which she can be found in the Bible'; 4. Some characteristics of its post-war edition of 1966, revised by Miskotte himself, added utterances on new frontiers (e.g. questioning all authority, the ‘death of God'). With such a multi-layered text as its result, one can understand why the English translators return to the more unequivocal edition of 1941.